Flexible and freestanding MoS2/rGO/CNT hybrid fibers for high-capacity all-solid supercapacitors. (February 2021) - Jian, Xianlong; Li, Hongbian; Li, Hui; Li, Yunxing; Shang, Yuanyuan
Abstract: Flexible fiber supercapacitors (FSCs) have been considered as a promising energy supply for wearable and portable electronics due to their easy integration with fabrics. However, it is challenging to fabricate high-capacity FSCs without compromising their flexibility. Here, an FSCs with both high capacity and flexibility were fabricated by coating electroactive molybdenum disulfide (MoS2 ) nanoflakes on a CNT fiber backbone with rGO as the adhesion layer. The as-prepared MoS2 /rGO/CNT FSC exhibited a high areal capacitance of 93.2 mF cm −2 and an 85% capacitance retention rate after continuous 5000 cycling. Moreover, the MoS2 /rGO/CNT FSC was highly flexible and no performance decay was observed after 1000 cyclic bending. The MoS2 /rGO/CNT FSC provides a promising candidate to supply wearable and portable electronics. Graphical abstract: MoS2 /rGO/CNT hybrid fibers supercapacitor fabricated by coating electroactive molybdenum disulfide (MoS2 ) nanoflakes on a CNT fiber backbone with rGO as the adhesion layer exhibited high flexibility and cycling stability. Image 1